PEMIKIRAN POLITIK ISLAM TRADISONALISME: PEMIKIRANMU’TAZILAH - Ahmad Zaky Ramadhan; Aminuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
Studying the science of kalam is one of the most important aspects and is included as a fundamental component of faith. Firstly, we express it verbally; secondly, we implement it through the pillars with actions, and thirdly, we believe it in our hearts. To strengthen this conviction, it is crucial to delve into and comprehend the theology of kalam. In order to make our verbal expressions convincing and firm, we need the knowledge of theology, particularly the study of monotheism, which deals with the concept of divinity. This study of monotheism has evolved into the science of kalam. In this academic work, the author endeavors to elucidate the history of kalam, study the theology within kalam, especially focusing on the Mu'tazilah schools of thought within kalam theology. The aim is to enhance the understanding of Mu'tazilah, explore their origins, identify key figures, and examine their teachings. The author aims to address the issues surrounding these two groups, to comprehend kalam theology deeply, and to recognize the thoughts, works, ideas of theologians, as well as the various schools of thought that have emerged within kalam theology.The author employs two methods: firstly, by reading books and visiting campus and local libraries, and secondly, by utilizing the internet to access additional references. Thus, Mu'tazilah are considered as two of the theological schools within Islam that can be categorized as factions.